Mulher maravilha: corpo e figurino nas representações visuais da personagem na série de televisão e no filme. - Oliveira, Marianna Costa (2018)
The present work aimed to understand how the presence and the readaptations of heroines in the comic books are represented in others means of communication. For this, we opted by Wonder Woman figure, which was created by William Moulton Marston, a proponent of feminism, in 1941, the character became symbol of the emergence of a new type of woman in a universe that until then was dominated only by male heroes. As the uniform and the body are considered elements that are part of the imaginative composition of heroin, they were chosen to the analysis, which was performed in a comparative way between images and information that were available in several media researched. The analysis referred to three distinct moments of the character: the first was the Wonder Woman developed by Marston in 1941 to a Comic Book (CB), the second were the series Wonder Woman in 1975-79, developed to television; and the third was the film Wonder Woman by Patty Jenkins in 2017. All episodes of the television series were starred by Linda Carter, as well the films that involved the heroine and had as protagonist Gal Gadot, and all six first editions of each arc, were studied. To discuss the main events responsible for the emergence of comics were used the authors Goidanich, Reblin, Viana and Lepore. To discuss about the cinema, its evolution, adaptations and its relation with comics, were used as theoretical basis the authors Guimarães, Parente, Deleuze, Jenkins; in order to understand how the body is shaped and modified according to the dominant culture and to do a relation with the costumes chosen to the character, were used the authors Reblin, Fischer, Costa, Bustamente and Lipovetsky. It was also presented the complete historical course of the character, from its conception to the present day for this discussion were used Crawford, Lepore, Greenberger, Lyons, Levitz, Vergueiro and Straczynski. A comparative analysis was made between the body and the costume of Wonder Woman, where was evaluated all the components of the heroine costumes, comparing them between their inspirational versions and between the versions of the cinema and the television. Was discussed the meaning of modifications in these elements through Lepore, Laver and Reed. Was possible to verify, as the result, that the representativeness of the Wonder Woman in the comics since its inception to her cinematographic adaptations was carried through her body and costumes, once they were fundamental elements that conveyed her convictions, showing that there is a connection between the heroine and the way she was presented.